Persepsi Non-Muslim Terhadap Perbankan Syariah di Kota Banda Aceh: Indonesia - Muliza, Muliza (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2022)
The implementation of Qanun Aceh number 11 of 2018 has given a new face to the financial industry in Province Aceh. The qanun stipulates that every bank carrying out its activities in the Aceh region must be based on sharia principles. This study aims to see how the Non-Muslim community's perception of the interest in using Islamic banking products in Aceh. The population in this study were all Non-Muslim communities living in the city of Banda Aceh, amounting to 4,827 people, while the sample was taken using the Slovin formula so that 100 samples were obtained. Data collection techniques were carried out by interviewing 10 informants and distributing questionnaires to 100 samples. The method used in this study uses mixed methods.The results of qualitative interviews and qualitative results from the distribution of the questionnaire were analyzed quantitatively by performing multiple linear regression analysis. The results show that in general, non-Muslim communities hope that in Aceh, not only Islamic banking operates but also conventional banking, as before the enactment of Qanun 11 of 2018, making it easier to carry out financial and business transactions. Based on the regression results, it is also found that cognitive perception variables (X1), affective perceptions (X2) and conative perceptions (X3) affect the interest (Y) of non-Muslims in using islamic banking in Banda Aceh.